Peritonitis due a perforated primary intestinal Hodgkin's lymphoma - Armand Ugon, César; Otazu, Heber; Burastero, Mercedes (Cirugía del Uruguay, 1983)
A case of perforated primary intestinal Hodgkin's lymphoma in the abdominal cavity is presented.